Alcohol dependency as an avoidance behaviour from panic disorder: a case study - Karaaziz, Meryem; Baştuğ, Bahar; Sökmez, Tijen (Journal of Dependence, 2015)
Panic disorder and alcohol abuse are two psychiatric disorders which are commonly seen together. Especially in the last 50 years, these two diagnoses have been found to be interrelated, and this relationship has been described using the term ‘self-medication’. This study presents a case involving alcohol use for the purpose of self-medication following panic attack that was evaluated using projective techniques.
Keywords: Panic disorder; Alcohol abuse; Thematic Apperception Test